2024
DOI: 10.3390/cryst14010097
|View full text |Cite
|
Sign up to set email alerts
|

The Formation of Supramolecular Chiral Materials from Achiral Molecules Using a Liquid-Crystallin System: Symmetry Breaking, Amplification, and Transfer

Atsushi Yoshizawa

Abstract: Recently, the formation of chiral materials by the self-organization of achiral small molecules has attracted much attention. How can we obtain chirality without a chiral source? Interesting approaches, such as mechanical rotation, circularly polarized light, and asymmetric reaction fields, have been used. We describe recent research developments in supramolecular chirality in liquid crystals, focusing primarily on our group’s experimental results. We present the following concepts in this review. Spontaneous … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 109 publications
0
1
0
Order By: Relevance
“…Niori et al discovered ferroelectric switching in a tilted smectic B2 phase of the achiral bent-core molecule P-n-O-PIMB in 1996 [14], and then Sekine et al suggested chirality in the smectic B2 phase [15]. These findings opened new avenues for the study of polar order and chiral superstructures in liquid crystals [16][17][18][19][20]. Ferroelectricity was observed in a uniaxial smectic A phase of a bent-core molecule [21].…”
Section: Introductionmentioning
confidence: 98%
“…Niori et al discovered ferroelectric switching in a tilted smectic B2 phase of the achiral bent-core molecule P-n-O-PIMB in 1996 [14], and then Sekine et al suggested chirality in the smectic B2 phase [15]. These findings opened new avenues for the study of polar order and chiral superstructures in liquid crystals [16][17][18][19][20]. Ferroelectricity was observed in a uniaxial smectic A phase of a bent-core molecule [21].…”
Section: Introductionmentioning
confidence: 98%